A Dynamic Analysis of a Record Breaking Winter Season Blocking Event - Andrew D. Jensen (Advances in Meteorology)
The objective of this work is to study in detail a strong North Pacific, large amplitude, and long-lived blocking event that occurred during January 23–February 16, 2014. Indeed, it was the 11th strongest Northern Hemisphere event lasting longer than 20 days since 1968. This event formed out of the strong ridge that was associated with the devastating drought in the Western United States during the winter season of 2013-2014. This blocking event had many outstanding dynamical characteristics, the chief of which was that it survived an abrupt change in the planetary-scale flow when the Pacific North American pattern index changed from positive to negative in early February. The block then reintensified and persisted into mid-February. Several diagnostic techniques are employed to investigate the change in the planetary-scale flow during early February 2014 that have been applied to blocking before but aren’t as well known in the blocking literature.